FAVORIT F35 102, VERKLINGENDE TROMMELN: Mit Max Lersch im unbekannten Afrika. One 12-inch mono disc of Austrian production. Distributed in Germany by Electrola Gesellschaft mbH, Maarweg 149, D-5 Koln-Braunsfeld. (International Library of African Music, 1969)
This well recorded L.P. is also the product of a filming team in Africa. With less crew and less dollars they have also tried to give a representative picture of the variety of cultures and ways of life in Africa. The record is similar to the one reviewed above in that it also aims at giving an impression of the large musical styles of the continent.
Keywords: African Music